Glucose tolerance in normal pregnancy - Calderon, Rolando (2015)
In a group of 21 third trimester pregnant women the intravenous glucose tolerance test in one hour was performed. For comparison a group of 15 non pregnant women matched for age were submitted to the same procedure. There is a significant lower level of fasting blood glucose in the pregnant group and also at 15 and 60 minutes during the intravenous glucose tolerance test. It is concluded that normal pregnancy is associated with a lower level of fasting blood glucose and an improvement in the tolerance to glucose. The results of the present work must be taken into account when an interpretation of glucose tolerance during pregnancy is made.